Banda Aceh استخدام كتاب اللسان العربي بوسيلة التدريبات لترقية قدرة الطلاب على التعبير التحريري لدي الطلاب بمعهد باب النجاح - Maknum, Hurul; Muslim, Buhori; Badruzzaman, Badruzzaman (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2024)
Researchers chose the research title “Using lisanul arabic book through practice questions to improve students' ability in Ta'bir Tahriri at Babun Najah” Islamic Boarding School. Researchers wanted to study this research because based on initial observations it was found that students were unable to write sentences and paragraphs according to correct grammatical rules, and they were weak in forming perfect sentences in learning Ta'bir. This research aim to identify the effectiveness of using the lisanul arabic book through question exercises to improve students' ability to express writing and to identify students' responses in using the lisanul arabic book in learning to write Ta'bir Tahriri. The research method in writing this research is experimental research. In collecting data, researchers carried out pre-tests, post-tests and questionnaires. The population used in this research was all students at the babun najah islamic boarding school, Banda Aceh. The sample in this study was students in grade 2 MTs (C) with 32 people. Researchers obtained research results that learning ta'bir tahriri using the lisanul arabic book students' abilities in Ta'bir Tahriri. Researchers rely on test results (T-Test) at the significance level (sig.) (0,00 smaller than 0,05), and this shows that the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is acceptable. Learning ta'bir tahriri using lisanul arabic book improves students' ability to write ta'bir tahriri, this is based on the answers in the questionnaire, students choose (strongly agree) and this is based on the student's response to the questionnaire with a score of 82,2.